A Case of Neurologically Intact Survival after 2 hours and 50 minutes of Euthermic Cardiac Arrest Treated with Mechanical CPR and Intra-arrest Percutaneous Coronary Intervention. (4th May 2019) - Burnett, Aaron Michael; Frascone, Ralph J.; Brechtken, Johannes; Warren, David; Roach, Brian; Zinkel, Andrew R.
Abstract: We report a case of a 56 year old male in ventricular fibrillation (VF) cardiac arrest for a total of 2 hours and 50 minutes who was diagnosed with ST elevation myocardial infarction (STEMI) during a brief 10 min period of return of spontaneous circulation (ROSC). The patient underwent successful percutaneous coronary intervention (PCI) while receiving mechanical chest compressions for ongoing VF. Our case demonstrates the potential for neurologically intact survival in VF cardiac arrest patients despite prolonged periods of VF who are treated with mechanical CPR and intra-arrest PCI.